MacCallister [large type] : the Eagles legacy : ten guns from Texas - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. MacCallister, the eagles legacy (Series), 2017)
"When Duff MacCallister journeys to Texas to deliver 100 head of Angus cattle, he finds a land on fire. Lawless teams of fence cutters, branded Blue Devils by the locals, are rampaging across grazing land in the name of an easter land company. The ranchers are fighting back, and Duff joins the fray. But the fight leads to Austin, and into an even deadlier mission: the governor's daughter has been kidnapped by Blue Devils. Duff and his partner Elmer are wiling to go after her, but they're going to need more men and a lot more firepower." -- Back cover.